2013
DOI: 10.6007/ijarbss/v3-i10/285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quality of Work Life on Organizational Commitment by SEM (Case Study: OICO Company)

Abstract: Nowadays, according to the importance of human resources in advancing the goals of the organization, improving the quality of work life has become one of the main goals of the organizations. Main purpose of this study is to analyses the effect of quality of work life (adequate and fair compensation, safe and healthy environment, growth and security, development of human capabilities, the total life space, social integration, constitutionalism, social relevance) on organizational commitment of employees of OICO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 9 publications
1
26
0
7
Order By: Relevance
“…12, No. 12;2017 development. This study was applied in foreign banks only and will be of added value if applied to commercial banks of Jordan Based on the results of this study we recommend the following: Provide new methods of work, in addition to providing attractive tools and modern work for individuals working within the banks, which reflects positively on its performance in the provision of service.…”
Section: Discussion Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…12, No. 12;2017 development. This study was applied in foreign banks only and will be of added value if applied to commercial banks of Jordan Based on the results of this study we recommend the following: Provide new methods of work, in addition to providing attractive tools and modern work for individuals working within the banks, which reflects positively on its performance in the provision of service.…”
Section: Discussion Recommendationsmentioning
confidence: 99%
“…Also the previous studies showed that organizational commitment can be subdivided into three major components namely: continuance commitment, normative commitment, affective commitment (Meyer & Allen, 1991). In this study, affective commitment will be depended on to measure the organizational commitment, as it is considered as the optimal component of an organizational commitment (Parvar et al, 2013).…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 3 more Smart Citations